(untitled) (The Research of Medical Science Review, 2025)
Background: Polycystic ovary syndrome (PCOS) is a common hormonal disorder with metabolic complications. While metformin is widely used, newer drugs like empagliflozin show promise. Due to limited local data, this study evaluated empagliflozin’s effects on metabolic parameters in women with PCOS in a local population. Objective: To compare the effect of empagliflozin on metabolic parameters in polycystic ovary syndrome in comparison with metformin in terms of mean difference in body mass index and fasting blood glucose (8 hrs fasting). Duration: 25-11-2024 to 25-05-2025 Methodology: Following approval from the Ethical Review Board, 60 PCOS patients from DHQ hospital Sheikhupura were enrolled and randomly assigned to two groups using the lottery method: Group A received empagliflozin 25 mg daily, and Group B received metformin SR 1500 mg daily for 12 weeks. Baseline and 12-week BMI and fasting glucose levels were recorded. BMI was calculated using the standard formula, and blood glucose was measured from a single hospital lab by one operator to minimize bias. Results: This study on 60 PCOS patients (mean age 32.73 ± 6.28 years, BMI 29.95 ± 3.02) showed greater BMI (−1.80 vs. −1.01 kg/m²) and glucose (−16.27 vs. −13.83 mg/dL) reductions with empagliflozin than metformin. Subgroup trends favored empagliflozin, though some lacked statistical significance due to limited sample sizes. Conclusion: Empagliflozin demonstrated superior efficacy over metformin in reducing BMI and fasting blood glucose in women with PCOS over 12 weeks. Although end-treatment values were comparable, the magnitude of reduction was significantly greater with empagliflozin. Subgroup trends favored empagliflozin, though some lacked statistical significance, likely due to limited sample sizes.